1988
DOI: 10.1136/adc.63.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Age dependence of flow velocities in basal cerebral arteries.

Abstract: SUMMARY Flow velocities in the basal cerebral arteries were studied by transcranial Doppler sonography. A longitudinal study was undertaken on 25 healthy newborn babies during the first 20 days of life, and a cross sectional study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
106
0
8

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 17 publications
(1 reference statement)
11
106
0
8
Order By: Relevance
“…the time it takes blood to flow from the labeling slab to the imaging slices. Previous studies (29,30) have shown that flow velocities in the basal cerebral arteries and carotid arteries are lower in neonates than in adults. It is therefore reasonable to assume that a TI 1 of 700 ms, which was optimized in adults, fulfills the abovementioned first condition in neonates as well.…”
Section: Discussionmentioning
confidence: 99%
“…the time it takes blood to flow from the labeling slab to the imaging slices. Previous studies (29,30) have shown that flow velocities in the basal cerebral arteries and carotid arteries are lower in neonates than in adults. It is therefore reasonable to assume that a TI 1 of 700 ms, which was optimized in adults, fulfills the abovementioned first condition in neonates as well.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos sobre a dopplerfl uxometria pela ultra-sonografi a transfontanela em recém-nascidos têm sido realizados, demonstrando um declínio fi siológico progressivo do IR com a idade cronológica 16 , e alterações dos valores de IR em condições patológicas, como por exemplo na hipóxia [17][18][19][20][21][22][23][24][25] . Porém este pare- Em estudos correlatos utilizando o Doppler transfontanela para a avaliação da EHI em RN a termo, não foram excluídos RN com alterações morfológi-cas detectadas pela USTF [17][18][19][20][21][22][23] .…”
Section: Discussionunclassified
“…Normal RI values are typically higher in premature infants (< 33 weeks' gestational age: 0.77 ± 0.09; > 34 weeks: 0.70 ± 0.07) and gradually decrease to a mean value of 0.50 during the first 1 to 2 years of life. 9,30 Our available study and control populations differ in median age, and this may have introduced bias into our study results, especially in the cutoff points between normal and abnormal RI values as determined by our ROC analysis. Nonetheless, we believe our results accurately reflect the mix of diagnoses and age groups that can be encountered in daily clinical practice in that ventriculomegaly is more likely to be associated with elevated ICP in younger than in older children, in whom loss of brain parenchyma due to neonatal insult has become more manifest.…”
Section: Discussionmentioning
confidence: 99%